An analytic model of typhoon wind field and simulation of storm tides - Sun, Zhilin; Ding, Kaixuan; Li, Zongyu; Chen, Fanjun; Zhong, Shanhong (Frontiers in Marine Science, 2023)
Storm tides have intensified due to global climate warming, with limited attention given to storm current velocity (SCV) due to data scarcity during hurricanes/typhoons and limitations in existing wind models’ accuracy. We propose an analytic model incorporating sea-surface resistance into the gradient wind equation, offering a theoretically robust approach. Through rigorous verification against measured data, our model demonstrates significant accuracy improvement compared to established models. Simulating storm tides during Typhoon Rammasun using our approach reveals strong agreement between calculated SCVs and measured data, surpassing the performance of the Holland model. Notably, typhoon storm surges primarily respond to pressure, while SCVs are predominantly governed by wind speed in open sea. The highest water level aligns with the lowest pressure, with maximum SCVs trailing the maximum wind radius. SCVs significantly exceed astronomical tidal current velocities (ACVs) in the open sea, reaching a maximum of 3.57 m/s. Areas where the SCV-to-ACV ratio exceeds 3 constitute 21.4% of the study area. Combining our wind model with Typhoon SCV simulations provides valuable insights into storm tide dynamics, advancing our understanding of storm tide mechanisms and informing mitigation strategies.